Peran Pendidikan Pancasila Dalam Membangun Karakter Demokratis Siswa Melalui Partisipasi Pemilu Osis Di Sma Negeri 5 Halmahera Timur - Marcelina Yuli Andiyani; Putri Nanda Sari Dewi; Lutfiah Farlianti; Sriwidya Boro; Febi Sa`'Pangallo; Khusnul Fatimah (PT. Citra Media Publishing, 2025)
Democracy is applied not only at the national level but also in schools as a foundation for character building among students. The OSIS election at SMA Negeri 5 Halmahera Timur serves as a tangible implementation of democratic principles, with the aim of analyzing the role of Pancasila education in shaping students' democratic character through participation in the OSIS election. This research uses a descriptive qualitative approach, with data collection through observation, interviews, and documentation. The research results show that the student council elections were conducted transparently and systematically, involving students in the processes of debate, campaigning, and voting. This activity helps students apply the values of Pancasila democracy, especially the fourth principle regarding wisdom in deliberation. In addition, the student council elections enhance students' leadership, participation, and critical thinking skills. Overall, this activity proves that Pancasila education through OSIS elections can shape students' democratic character, preparing them to become future leaders, despite the presence of several supporting factors and challenges in integrating Pancasila values.